DIMENSI-DIMENSI PERSEPSI RISIKO KESELURUHAN KONSUMEN - Retno Wulandari (Jurnal Riset Manajemen dan Bisnis, 2012)
This study examined a model of determinants of consumer’s perception of risk of frequentlyused product, laptop computer. Data was gathered from the survey questionnaire. The samplewas drawn upon students at major school of business, conveniently. Three indicators wereused to capture overall risk, and three for each of six risk dimensions. Using six variablesthat had been presumed by researches, multiple regression model was developed for thisanalysis. This study showed that only social risk, financial risk and psychological risk weredetermining factors of overall perceived risk. These imply to marketer that they should relyon these risks that predominantly affect in consumer buying decision.Keywords: perception of risk, social risk, financial risk, psychological risk.